FAIR WEALTH DISTRIBUTION THROUGH INSTRUMENTS IN ISLAMIC ECONOMICS - Sri Gusti Rezeki; Veri Ferdiansyah; Yunda Adisa; Dea Cindi Amelia Ginting; Rizqa Amelia (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
Distribution plays a crucial role in ensuring fair allocation of resources and commodities to individuals in a community, with the objective of achieving maslahat (benefit). In Islamic economics, distribution has a broader significance compared to other economic systems, encompassing the fair distribution of resources, goods, and services through market mechanisms, enabling individuals to experience the benefits of produced commodities. This research aims to examine the importance of fair wealth distribution in Islam using principles such as waqaf, qard al-Hasan, musharakah, mudharabah, zakat, and infaq. Employing a qualitative methodology, data was collected from papers, research journals, books, and written sources, which were reviewed, interpreted, and analyzed through content analysis. The findings indicate that distribution instruments in Islamic economics serve as effective means to achieve fair and equitable distribution within society. By implementing waqaf, qard al-Hasan, musharakah, mudharabah, zakat, and infaq, communities can attain social justice and reduce economic disparities. However, public awareness, adequate infrastructure, and a supportive regulatory framework are crucial factors for the successful implementation of these distribution instruments. Through appropriate efforts, these instruments can become powerful tools in fostering a more inclusive, sustainable, and just economy.